The Effect Of Online Business Resources And Capabilities On Business Performance In Malaysian Fashion Industry - Teo, Shao Zhen (2022)
The advancement of information technology in addition with internet access has revolutionized trades which involve buying and selling of goods and services in the virtual platform. The government has been striving to boost online business establishments and this effort is rising in Malaysia. Nevertheless, it was discovered that there was only 6.3% contribution by online business market in terms of the gross value added to the gross domestic product (GDP) in the year 2017 although the government has been striving to establish online business in Malaysia. Grounded on Resource-Based View (RBV) theory and Dynamic Capability View (DCV) theory, the current research examined the effect of online business resources (relational resources, financial resources and human capital) and online business capabilities (digital marketing capability, CRM capability and IT capability) on online business performance. Besides that, the direct relationship between online business resources and online business capabilities were also been tested. In addition, this study also investigated whether firm competitiveness mediates the relationship between online business capabilities and online business performance. Using a purposive sampling technique, data was obtained from 98 online business in Malaysian fashion industry, including apparel, footwear and accessories sectors. The data was analysed using Partial Least Squares structural equation modelling (PLS-SEM). Results discovered that there was relationship existed between some aspects of online business resources and online business capabilities. According to the results, financial resources only have positive and significant effect to IT capability.